Experimental Study of Test Room Air Conditioning Using Solar Cold Energy Storage - Ambarita, Himsar; Goldwin, Albert; Samar (International Journal of Architecture and Urbanism, 2026)
In tropical regions, air-conditioning systems are among the main contributors to building energy consumption, and their energy demand may account for more than half of the total building load. Therefore, improving cooling efficiency has become an important issue in current building energy management. This study experimentally investigates a solar-powered room cooling system using cold energy storage to reduce the air temperature in a test room with dimensions of 4.8 m × 3.7 m × 3.3 m. The proposed cooling unit combines thermoelectric cooling technology with an actively operated phase change material as the cold storage medium. In this active configuration, heat exchange between the indoor air and the PCM is enhanced through forced convection supported by additional mechanical components. The experimental results show that the system was able to lower the indoor air temperature to 26.75 °C and achieve a relative humidity of 58% when the average outdoor temperature was 29.55 °C. The maximum coefficient of performance of the CES system reached 0.7, with an average value of 0.39 during the first day of operation.